Synthesis and Characterization of Silver- and Dysprosium-doped Zinc Oxide Structures - Ateş, Tankut; Keser, Serhat; Bulut, Niyazi; Kaygili, Omer (Niyazi BULUT, 2025)
In this study, silver (Ag) and dysprosium (Dy) doped zinc oxide (ZnO) samples were prepared using the wet chemical route, and characterized by X-ray diffraction (XRD), scanning electron microscopy, and energy dispersive X-ray (EDX) spectroscopy. For all the samples, a single phase of ZnO was observed. The addition of these dopants and their amounts affected the lattice parameters, bond lengths, and bond angles of the ZnO structure. The morphology was affected by the amount of these elements as used in this study. The EDX spectroscopy results supported the incorporation of these dopants into the ZnO lattice.
Keywords: Condensed Matter Physics (Other); Yoğun Madde Fiziği (Diğer)